Pengaruh Konsumsi Sari Buah Jambu Merah dan Madu terhadap Kenaikan Nilai HB pada Ibu Hamil di Tempat Praktek Mandiri Bidan Muarofah Surabaya - Ratna Indriyani; Aulia Aulia; Maulana Widi Andrian; Emdat Suprayitno (Fakultas Ilmu Kesehatan, 2020)
ABSTRAK Pregnancy is one of the Physiology things but, in the process of pregnancy not a little pregnant mothers that experienced the problem like Anemia disease. The Aim of the research is To Known the effect in giving the red Guava juice and honey into the e knhancement HB level for the Pregnant Women in semester two and semester Three by the Light anemia. The method employed in this research was Experimental Quasy by Up Design Non equivalent Control Group pre test and post test design . the instrument or the sample of this research is the pregnant mothers in semester two and semester three consists of 32 as informants and they are will divide into the two groups as follows: 16 Respondent in treatment groups and 16 respondent in control groups. The technique that used in this research was accidental sampling. The data was collected by using observation task. The data will analyse by using Wilcoxon test. The result of the research that the level of Pregnant mother’s HB before Giving the Red Guava Juice and honey is in the average level of 9,81. The HB level of pregnant mother’s after Giving the Red Guava Juice and honey most of the levels of Pregnant Mother’s HB was increased in the treatment group in the average level of 10,25 gr %, while in the control group have no found the differentiated of the HB level before and after the treatment in average level of 9,81 gr % by the result of the Wilcoxon test analyse p=0,000 (p<0,05). Based on the previous analysis above writer would like to draw some conclusion as follows: the sicnificant influence in giving the Red Guava Juice and honey to increase the HB levels of pregnan mother’s. its expected all the pregnant women to Check up routine about the HB level to knowing early the Anemia’s effect in Pregnancy so that it cawill be taken by the Preventive treatment Keyword: Anemia, Hb, pregnant mother